2019
DOI: 10.1101/654350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence of the Cost-Efficiency of Scale as seen in Polio Vaccination and Surveillance Costs

Abstract: 9 This analysis examined how polio program costs vary with scale for vaccination and disease surveillance, 10 based on historical budget data published by the Global Polio Eradication Initiative (GPEI) from 2005 to 11 2018. We applied a linear mixed effects regression model in order to understand the cost structure of 12 the historical GPEI budgets, with the goal that lessons learned from polio may be extended to other 13 global disease elimination programs. Our findings demonstrate that there are economies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Tebbens [8] examined the total cost of the global polio laboratory network (including both environmental and case surveillance) and concluded that true total costs were higher than budgeted for, while Hagedorn et al [9] found that there were economies of scale for surveillance programs. Given this, cost estimates for a future typhoid ES system must consider costs of implementation not for a single sampling site, but when expanded to cover large geographic regions and higher volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Tebbens [8] examined the total cost of the global polio laboratory network (including both environmental and case surveillance) and concluded that true total costs were higher than budgeted for, while Hagedorn et al [9] found that there were economies of scale for surveillance programs. Given this, cost estimates for a future typhoid ES system must consider costs of implementation not for a single sampling site, but when expanded to cover large geographic regions and higher volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has examined the total cost of the global polio laboratory network (including both environmental and case surveillance) and suggested that true total costs were higher than budgeted 8 , but they are also subject to economies of scale 9 . Given this, cost estimates for a future typhoid ES system must consider costs of implementation not for a single sampling site, but when expanded to cover large geographic regions and higher volumes.…”
Section: Introductionmentioning
confidence: 99%